Оцінка показників фізичного розвитку та функціонального стану студенток спеціальної медичної групи = Assessment of indices of physical development and functional status of female students of a special medical group - Grygus, I. M.; Petruk L. А. (Journal of Education, Health and Sport, 2015)
Grygus I. M., Petruk L. А. Оцінка показників фізичного розвитку та функціонального стану студенток спеціальної медичної групи = Assessment of indices of physical development and functional status of female students of a special medical group. Journal of Education, Health and Sport. 2015;5(10):158-169. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32585 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A158-169 https://pbn.nauka.gov.pl/works/661259 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 20.10.2015. Оцінка показників фізичного розвитку та функціонального стану студенток спеціальної медичної групи Assessment of indices of physical development and functional status of female students of a special medical group Григус І. М., Петрук Л. А. Grygus I. M., Petruk L. А. Національний університет водного господарства та природокористування, м. Рівне, Україна National University of Water Management and Nature Recourses Use, Rivne, Ukraine Annotation Introduction of new technologies into the learning process, a dramatic increase in the volume of information, the advantage of harmful habits over a healthy lifestyle – all the above factors have a negative influence on the organisms of young generation. The complex of the above factors contributes to the occurrence and exacerbation of cardiovascular, neurologic, psychiatric, gastrointestinal and other diseases; it affects the motor performance, working capacity, success rate, physical development and physical fitness of students. There has been examined the dynamics of the numerical composition of the students belonging a special medical group for the period of six last years and there have been determined ICD diseases of the students. The research involved 172 female students of the age ranging from 17 to 20 who are placed in a special medical group because of the state of their health. In order to determine the level of the physical development there have been analyzed anthropometric indices and assessed functional abilities of cardiovascular and respiratory systems. There has been ascertained that the number of the university students who are placed in a special medical group because of the state of their health constitutes 19,8 % and it gradually increases each year, although general admission of students decreases. The most widely-spread diseases among the above category of students are pathologies of cardiovascular system (47,6 %), musculoskeletal system (17,5 %) and visual organ disorders (10,6 %). There has been assessed the functional conditions of cardiovascular and respiratory systems and ascertained that the obtained results are within age and gender physiological norms. There has been calculated the Ruffier index which shows the low level of physical working capacity of female students of a special medical group. Physical development, physical fitness and functional status of female students of a special medical group are below average and within age norms. Key words: special medical group, state of health of students, physical development, functional indices. Анотація Впровадження новітніх технологій у навчання, різке зростання обсягу інформації, перевага шкідливих звичок на противагу здоровому способу життя – все це негативно впливає на організм підростаючого покоління. Сукупність таких факторів сприяє виникненню та загостренню серцево-судинних, нервових, психічних, шлунково-кишкових та інших захворювань, позначається на руховій активності, працездатності, успішності, фізичному розвитку та фізичній підготовленості студентів. Розглянуто динаміку кількісного складу студентів спеціальної медичної групи за останні шість років та визначено нозології студентів. У дослідження було включено 172 студентки віком 17-20 років, які за станом здоров’я віднесені до спеціальної медичної групи. Для визначення рівня фізичного розвитку були проаналізовані антропометричні показники та оцінені функціональні можливості серцево-судинної та дихальної систем. Встановлено, що кількість студентів університету, які за станом здоров’я віднесені до спеціальної медичної групи, становить 19,8 % та з кожним роком зростає, хоча загальний набір студентів зменшується. Найбільш поширені захворювання серед цієї категорії студентів складають патології серцево-судинної системи (47,6 %), опорно-рухового апарату (17,5 %) та органів зору (10,6 %). Оцінено функціональний стан серцево-судинної та дихальної систем і встановлено, що отримані дані знаходяться в межах статевовікових фізіологічних норм. Обраховано індекс Руф’є, який свідчить про низький рівень фізичної працездатності студенток спеціальної медичної групи. Фізичний розвиток, фізична підготовленість та функціональний стан студенток спеціальної медичної групи знаходиться на рівні нижче середнього та в межах вікових норм. Ключові слова: спеціальна медична група, стан здоров’я студентів, фізичний розвиток, функціональні показники.